Penilaian Aktivitas Antioksidan dalam Ekstrak Bunga Telang (Clitoria ternatea L.) Menggunakan Uji DPPH dengan Berbagai Pelarut - Najwa Firida Rahma; Wilda Tsabitah Jafnah Mahmud; Auliya Ika Putri; Salsabiila Wina Delia; Ainul Ghurri (CV. ITTC INDONESIA, 2026)
Butterfly pea (Clitoria ternatea L.) is a plant that contains several bioactive compounds, including flavonoids and anthocyanins, which can act as natural antioxidants. The level of antioxidant activity depends on the type of solvent used in the extraction process. This review article talks about evaluating the antioxidant activity of butterfly pea flower extracts based on the use of different solvents using the DPPH technique. The approach taken is a literature review from various publications discussing butterfly pea flower extraction using ethanol and water solvents through maceration, remaceration, infusion, soaking, and decoction methods. The results show that the IC50 values of butterfly pea extracts vary from very strong to weak depending on the solvent type and extraction method used. Ethanol usually works better as an antioxidant than water because it’s more effective at extracting bioactive molecules. Based on many studies that were reviewed, it can be concluded that the choice of solvent affects the antioxidant activity of butterfly pea flower extract.